Rag Proteins Regulate Amino Acid-Induced mTORC1 Signaling - Sancak, Yasemin (2009)
The serum and nutrient-sensitive protein kinase mTOR is a master regulator of cell growth and survival. The mechanisms through which nutrients regulate mTOR have been one of the major unanswered questions in the mTOR field. Identification of rag family of GTPases as mediators of amino acid signaling to mTOR is an important step towards understanding this mechanism.